TL 18177 - Epidemiological profile of sesamoid disorders of the first metatarsophalangeal joint - Rassweiler Hardt, Marcelo; Bergamaschi Demore, André; Kim, Antônio; Marcantonio Camargo, Leandro; Claudino Barbosa, Carolina; Machado, Samuel (Scientific Journal of the Foot & Ankle, 2019)
Introduction: The sesamoid bones are part of the hallux metatarsophalangeal (MTTF) joint complex and are an important factor in the normal biomechanics of gait. Abnormalities of the sesamoid bones are not rare but are often underestimated and include acute fractures, osteochondral lesions, bipartite sesamoids, recurrent traumatic sesamoiditis or infection, in addition to osteoarthritis. Given the lack of recent studies on the epidemiological profile of sesamoid-related diseases, the objective of this study is to identify the epidemiological characteristics of patients with these disorders. Methods: The study was approved by the research ethics committee and registered in the Brazil Platform (Plataforma Brazil). This retrospective study was performed by reviewing the electronic charts of foot and ankle outpatients diagnosed with sesamoiditis and acute or stress fractures between February 1, 2013 and January 31, 2018. The exclusion criterion used was the presence of incomplete records in the electronic chart. The following variables were analyzed: sex, age, occupation, participation in sports, laterality and affected sesamoid bone (medial or lateral). The data collected were tabulated and saved in an Excel spreadsheet and analyzed using descriptive statistics. Results: Data on 108 patients were collected after reviewing the charts. Based on these data, we report the epidemiological characteristics of patients with sesamoid disorders in a sample of orthopedic patients from a reference hospital of the Unified Health System (Sistema Único de Saúde – SUS) in a city in southern Brazil. Among the various occupations reported, the 3 most common were cleaner (29), student (23) and salesperson (16). Among the subjects who participated in sports, only 22 were involved in competitive sports (professional or amateur).